An Adaptive Neurocontroller for Induction Motors - Girovsky, Peter; Zilkova, Jaroslava; Timko, Jaroslav; Girovsky, Jan (Communications - Scientific letters of the University of Zilina, 2013)
The paper is focused on presenting possibilities of applying artificial neural networks (ANN) at creating a speed controller of an induction motor drive. The presented method of control takes advantage of approximating properties of multi-layer feedforward networks. The availability of the proposed neurocontroller is verified through the Matlab simulation. The effectiveness of the controller is demonstrated for different operating conditions and motor parameter changes of the drive system.